The Implementation of Guided Questions and Answers in Paragraph Writing through Online Learning - Dewi Safira Maulida; Nani Hizriani; Yokke Andini (ELITE JOURNAL, 2023)
Teaching writing online can be more challenging for teachers. Guided questions and answers is one of the teaching techniques used as a form of guidance from the teacher to their students in making a good paragraph. This study was conducted at MAN 3 Barito Kuala with the objectives to explore the implementation of guided questions and answers in paragraph writing through online learning and describe students' perceptions about it. This descriptive qualitative design was used to get a rich description of the results. To collect the data, observation, interview, and documentation were used as the instruments. The results showed that the teacher could implement guided question and answer well. Using WhatsApp as a digital device, the teacher completely applied the teaching stages from giving explanations to providing feedback for the students. Moreover, students' perception of the implementation of guided questions and answers through online learning was positive. Students agreed that the guided questions and answers technique through online learning could help them in writing a good paragraph. Keywords: Guided Questions and Answers, Paragraph Writing, Online Learning.